Indication and selection of pediatric patients for genetically modified T cells : for the SBTMO Technical manual of cellular therapy - Seber, Adriana (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
The use of CAR-T cells will completely change the treatment of many hematological diseases, including relapsed pediatric B-lineage acute lymphoblastic leukemia. This article is part of the Brazilian Society of Bone Marrow Transplantation (SBTMO)’s “Technical manual of cellular therapy” to guide physicians to select patients and indicate the use of the CAR-T cells in pediatric patients with acute lymphoblastic leukemia. Other aspects of CAR-T cell therapy and management of important toxicities are included on other articles of this volume.